Oligophrenin-1 (OPHN1), a gene involved in X-linked intellectual disability, undergoes RNA editing and alternative splicing during human brain development - Barresi, Sabina (2015)
Oligophrenin-1 (OPHN1) encodes for a Rho-GTPase-activating protein, important for dendritic morphogenesis and synaptic function. Mutations in this gene have been identified in patients with X-linked intellectual disability associated with cerebellar hypoplasia. ADAR enzymes are responsible for A-to-I RNA editing, an essential post-transcriptional RNA modification contributing to transcriptome and proteome diversification. Specifically, ADAR2 activity is essential for brain development and function. Herein, we show that the OPHN1 transcript undergoes post-transcriptional modifications such as A-to-I RNA editing and alternative splicing in human brain and other tissues. We found that OPHN1 editing is detectable already at the 18th week of gestation in human brain with a boost of editing at weeks 20 to 33, concomitantly with OPHN1 expression increase and the appearance of a novel OPHN1 splicing isoform. Our results demonstrate that multiple post-transcriptional events occur on OPHN1, a gene playing an important role in brain function and development.